The influence of lactoferrin on elemental homeostasis and activity of metal-containing enzymes in rats with Walker-256 carcinosarcoma - Lozovska, Yu.V.; Andrusishina, I.M.; Lukianova, N.Yu.; Burlaka, A.P.; Naleskina, L.A.; Todor, I.N.; Chekhun, V.F. (PH Akademperiodyka, 2023)
Summary. Aim: To investigate the content of essential elements (EE): copper, zinc, magnesium, iron and calcium and the evaluation of the activity of metal-containing enzymes — ceruloplasmin (CP), myeloperoxidase (MPO) and the content of transferrin (TF) in blood plasma (BP) and tumor tissue (TT) of animals with Walker-256 carcinosarcoma treated with lactoferrin (LF). Materials and Methods: The study of the EE content and the activity of the abovementioned enzymes was carried out on rats with Walker-256 carcinosarcoma treated with LF at the doses of 1 and 10 mg/kg of body weight. The quantitative content of EE in BP and TT of animals was determined using the inductively coupled plasma atomic emission spectroscopy (ICP-AES). Determination of CP activity, content of TF and hemochromes was performed using the method of electron paramagnetic resonance (EPR), and MPO — by unified biochemical method. Results: The introduction of LF at the doses of 1 and 10 mg/kg resulted in a decrease in the ratio of Cu/Zn in BP and even more expressed decrease of Ca/Mg ratio in TT. Administration of LF, especially at a dose of 10 mg/kg, affected the increase in CP and MPO activity in BP. It has been shown that administration of LF at a dose of 10 mg/kg led to an increase in oxidative products of destruction of the hemoglobin-hemochrom system in the TT, against the background of lowering the TF content. Conclusions: The administration of LF, especially at a dose of 10 mg/kg, led to metabolic alterations associated with inhibition of the tumor process. The detected modulating effect of LF on the content of the EE and the activity of the CP and MPO may be a basis for correction of the elemental balance in carcinogenesis.